Green Skills – Enablers of Transition to a Green Economy - HÜSEYNOVA, Arzu D.; RUSTAMOVA , Intizar; MAMMADOVA , Simuzar; MAMMADOVA, Intizar (Journal of Ecohumanism, 2025)
This article analyzes the importance of developing "green" skills and their role in economic development within the context of Azerbaijan. The primary issue lies in the lack of consensus regarding the definition of "green" skills, which reduces the effectiveness of coordinated efforts in this area. The development of "green" skills is not only related to the implementation of technologies but also to broader economic and ecological processes. The article proposes systematic forecasting of "green" skills, updating educational programs, and applying international standards. Based on international experience, the implementation of ecological technologies not only creates new jobs but also modernizes existing ones and increases labor productivity. Ultimately, the transition to a "green" economy is a critical strategic step for enhancing Azerbaijan’s economic and ecological potential.